Rabindranath Tagore the myriad-minded man - Dutta, Krishna; Robinson, Andrew (Bloomsbury, 1995)
This biography, the product of more than ten years of research and collaboration between the authors, is the first work in many decades to disentangle the profound and perplexing contradictions that made Tagore such a fascinating and pivotal figure. He was one of the very first to perceive that - despite the great geographic and cultural distance between them - East and West would be compelled to meet in the twentieth century